LAW, PRECARIOUS LABOUR AND POSTED WORKERS a sociolegal study on posted work in the eu. - Lasek-Markey, Marta ([S.l.] : ROUTLEDGE, 2023)
This book examines the role of law in regulating and influencing the lived experiences of posted workers in Europe. The posting' of workers is an unusual type of labour mobility, where workers are hired out to provide a specific service in another country. Although it involves a specialised area of law, it is one that serves as a magnifying glass for the long-standing tension between the economic and social dimensions of law's regulatory role. As an atypical form of labour migration, posting also touches upon broader themes concerning the role and purpose of labour law in a changing world of work. Taking up these themes through interviews with posted workers, lawyers and employers, the book adopts a sociolegal approach to consider how the law shapes the precarious lived experiences of posted workers in Europe. Giving voice to those with first-hand experience, the book goes on to propose solutions that might address the precarity of posted work. This book will be of interest to scholars, researchers and practitioners working in the areas of labour law, sociolegal studies, EU law, and migration.
Keywords: Labor laws and legislation -- European Union countries; LAW / Labor & Employment; BUSINESS & ECONOMICS / Labor